Antioxidant Potential and In Vitro Antidiabetic Activity of Paeonia japonica (Makino) Miyabe & Takeda Extract and Its Isolated Compounds - Jinfeng Yang; Hyun-Jung Seo; Yanjie Wang; Dan Gao; Nam-Ho Yoo; Ju-Hee Park; Eun-Soo Seong; Yong-Soo Kwon; Seung-Joong Kim; Myong-Jo Kim (Agronomy)
This study explored the potential of Paeonia japonica (Makino) Miyabe & Takeda (P. japonica) as a natural treatment for diabetes. A methanol extract of the root of P. japonica and its fractions were investigated for their antioxidant and antidiabetic properties. The ethyl acetate (EtOAc) fraction was the most potent, displaying strong antioxidant activity and inhibiting enzymes that break down carbohydrates (α-amylase and α-glucosidase), which could reduce blood sugar levels. Furthermore, the EtOAc fraction inhibited glucose uptake in 3T3-L1 cells and stimulated the gene responsible for cellular glucose uptake (GLUT4), suggesting improved insulin sensitivity. It also effectively reduced the formation of harmful advanced glycation end products linked to diabetic complications. The isolation of bioactive compounds from the EtOAc fraction revealed the presence of 4-O-methylgallic acid and ellagic acid, which potentially contributed to the observed antidiabetic effects. Overall, this study highlights the EtOAc fraction of P. japonica as a promising source for developing natural diabetes therapies. The findings suggest its potential for regulating various diabetic pathways, warranting further research for drug development.